MAKNA FILM BAGI MASYARAKAT ACEH - Permana, Rangga Mohamad; Puspitasari, Lilis; Indriani, Sri Seti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2019)
Films in Aceh didn’t seem to have any future ahead, especially after the armed conflict and the values and norms that were applied in Aceh. Most people in Aceh viewed films negatively because it was considered to have a negative influence towards the people and would also jeopardize the Islamic culture. Even cinemas were thought to be a place to do immoral things. Those statements made people in the film industry reluctant to build the business there. But after the great tsunami hit Aceh in 2004, documentary films arose. First, it was to inform the nation about the tsunami and its victims, but then it blossomed well throughout the years. This research is to describe the meanings of films for Aceh society, despite on its culture and its history. Data were collected based on qualitative research with a descriptive method. Data collection techniques are observation, depth interview, and documentation study. This research was conducted in Aceh, April 2018. Research result shows that there were two meanings of films for the people of Aceh, they are (1) as a ‘reflection’, which was shown in documentary films, and (2) as an ‘entertainment’, which was shown in comedy genre films.